2007
DOI: 10.1038/sj.npp.1301655
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Changes in Late Life Depression—a Structural MRI Analysis

Abstract: Multiple brain morphometric changes have been reported in late-life depression (LLD), mostly in studies comparing volumes of circumscribed brain areas. The aim of our study is to characterize the volumetric changes of multiple gray matter regions in relation to age of onset/duration of illness. We predicted that the association of gray matter volumes with total duration of illness and age of onset would differ depending on whether the region was susceptible to the toxic effects of chronic exposure to cortisol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
120
5
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 41 publications
5
120
5
2
Order By: Relevance
“…The majority of previous studies evaluating cortical volume loss in LLD have reported isolated regions of atrophy in LLD cortex (59), which in aggregate support extended neural network models of LLD, however integrating this data across studies is difficult due to methodological differences. Our findings of distributed reduction in cortical thickness in LLD is therefore significant and also largely consistent with the one previous study which has documented more distributed cortical volume loss in LLD (10). However, the degree to which our findings were almost exclusively seen in the right hemisphere was unanticipated and further study is warranted to determine if these findings are due in part to increased sensitivity of measures of cortical thickness over volumetric approaches to identifying cortical alterations in LLD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The majority of previous studies evaluating cortical volume loss in LLD have reported isolated regions of atrophy in LLD cortex (59), which in aggregate support extended neural network models of LLD, however integrating this data across studies is difficult due to methodological differences. Our findings of distributed reduction in cortical thickness in LLD is therefore significant and also largely consistent with the one previous study which has documented more distributed cortical volume loss in LLD (10). However, the degree to which our findings were almost exclusively seen in the right hemisphere was unanticipated and further study is warranted to determine if these findings are due in part to increased sensitivity of measures of cortical thickness over volumetric approaches to identifying cortical alterations in LLD.…”
Section: Discussionsupporting
confidence: 92%
“…However, the degree to which our findings were almost exclusively seen in the right hemisphere was unanticipated and further study is warranted to determine if these findings are due in part to increased sensitivity of measures of cortical thickness over volumetric approaches to identifying cortical alterations in LLD. In the previous study indicating a distributed pattern of cortical volume loss in LLD (10) laterality was not explored, so a direct comparison with our results is not possible. Nonetheless, our findings suggest that distributed reductions in cortical thickness may be a central morphometric abnormality associated with LLD and that cortical thinning in the right hemisphere may be particularly implicated.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…9,10 Finally, researchers have reported that the putamen is activated most strongly during anticipation of reward, whereas the caudate is activated most strongly during the receipt of reward. 8,10,11 A growing body of research indicates that adults with MDD have smaller volumes of the caudate [12][13][14][15] and putamen 13,14,16,17 than healthy controls. Postmortem studies have also reported smaller putamen volumes in depressed than in nondepressed adults.…”
Section: Introductionmentioning
confidence: 99%
“…Both methods involve spatial normalization of the brain images to a standard stereotactic space by registration to an atlas image. Automated ROI methods (or brain parcellation) are frequently used to study structural brain anomalies in schizophrenia patients (Lopez-Garcia et al, 2006;Yamasue et al, 2004) and recently are gaining popularity in aging research to demonstrate non-linear relationships between brain volumes and age (Andreescu et al, 2007;Terribilli et al, in press). …”
Section: Introductionmentioning
confidence: 99%